2016
DOI: 10.1074/mcp.m115.053421
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cellular Phosphorylation Signaling Pathways into Chromatin and Down to the Gene Level

Abstract: Protein phosphorylation, one of the most common and important modifications of acute and reversible regulation of protein function, plays a dominant role in almost all cellular processes. These signaling events regulate cellular responses, including proliferation, differentiation, metabolism, survival, and apoptosis. Several studies have been successfully used to identify phosphorylated proteins and dynamic changes in phosphorylation status after stimulation. Nevertheless, it is still rather difficult to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Approximately 80% of mammalian proteins are modified posttranslationally. For instance, phosphorylation is implicated in cell signaling , acetylation in epigenetics and NDs , ubiquitination in regulation of cellular protein homeostasis , hydroxylation in collagen formation , and glycosylation in the pathophysiology of neurotrauma . The basic findings from studies that demonstrated the role of PTMs in the relevant diseases are summarized in Table .…”
Section: Ptmsmentioning
confidence: 99%
“…Approximately 80% of mammalian proteins are modified posttranslationally. For instance, phosphorylation is implicated in cell signaling , acetylation in epigenetics and NDs , ubiquitination in regulation of cellular protein homeostasis , hydroxylation in collagen formation , and glycosylation in the pathophysiology of neurotrauma . The basic findings from studies that demonstrated the role of PTMs in the relevant diseases are summarized in Table .…”
Section: Ptmsmentioning
confidence: 99%
“…Although very promising, ChEP also has limitations, such as the inability to follow local changes in the protein abundance as a consequence of protein re-localization in specific chromatin regions and the fact that not all chromatin components may be fixed by formaldehyde. Chromatin constituents can also be characterized at the PTM level, as recently done by the phosphorylation specific-chromatin affinity purification (PS-ChAP) to monitor phosphorylation changes following activation or inhibition of global transcriptional patterns [75].…”
Section: Chromatin Constituentsmentioning
confidence: 99%
“…Chromatin constituents Mononucleosome and thiophosphorylation affinity enrichment [75] Peptide pull-down Chromatin readers Bait: peptides bearing a specific hPTM/sequence DNA reader affinity purification Chromatin readers Bait: DNA sequences [85,86] mChIP (modified chromatin immunoprecipitation)…”
Section: Proteomic Analysis Of the Chromatin Pelletmentioning
confidence: 99%